PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN DALAM INDEKS LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2012-2015 - Ricky Talumantak; Pamuji Gesang Raharjo (Panorama Nusantara, 2017)
This study attempts to analyze the influence of Probability Ratio (Earning Per Share, Return On Asset, Return On Equity, and Net Profit Margin) to stock prices. This study uses population to companies that listed on Indonesia Stock Exchange during 2012-2015. Number of companies as samples of this study are 38 companies for 4 years observation. Using to purposive sampling method, the total of this study are 152 financial reports. The testing of hypotheses in this study is use multiple regression and assisted by Eviews version 7.0 software. The results of the study indicate that the Net Profit Margin influences significantly to the stock prices. Meanwhile Earning Per Share, Return On Aset, and Return On Equity don’t influence significantly to the stock prices.